Influence of Interferences in the Relation Between Ampacity and Induced Voltage on Sheath in Double-Circuit Underground Lines - Guevara, Jesus E.; Colqui, Jaimis S. L.; Kurokawa, Sergio [UNESP]; Filho, José Pissolato (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper discusses the relationship between ampacity and induced voltages within the context of the four widely adopted configurations in double-circuit underground lines. This analysis considers two scenarios: one that accounts for underground interferences, which is the most exact, and another that solely considers the separation typically used in these duct banks. The results show that, with greater cable installation depth, a larger separation between cables is required to guarantee ampacity. The dependence between these values depends on the physical arrangement of the duct banks. Nevertheless, if this separation increases, the induced voltage on the sheath also will increase. Furthermore, it is sufficient to utilize the usual separation and increase this result by at least 2% when calculating the induced voltage on the sheath rather than considering the augmentation in phase spacing caused by underground interferences.
Keywords: Ampacity; induced voltages; residual induced voltage; underground interferences and duct banks